Bilateral congenital mucous extravasation phenomenon: A rare case with literature review - Hitesh Chander Mittal; Sunil Yadav; Sunita Malik; Monika Breta (Wolters Kluwer Medknow Publications, 2018)
The purpose of this paper is to discuss a rare case of bilateral congenital mucous extravasation phenomenon on buccal mucosa near commissure of mouth. The lesions were noted at birth, subsequently enlarged to interfere with feeding. The lesion frequently ruptured, regressed, and again enlarged to interfere with normal function. The lesions were surgically removed under general anesthesia at 11 months of age and the diagnosis was confirmed by histopathological examination. Postoperative follow-up after 14 months showed no recurrence.